PHARMACISTS’ PERCEPTIONS ON FACTORS CONTRIBUTING TO STOCK-OUTS OF ESSENTIAL MEDICINES AT A TERTIARY HOSPITAL IN SOUTH AFRICA: A QUALITATIVE CROSS-SECTIONAL STUDY. - Chuene , Tiisetso; France , Sogo (Student's Journal of Health Research Africa, 2024)
Background Essential medicines are one of the vital components in the provision of health services and their availability plays a crucial role in the reduction of mortality and morbidity associated with disease burden. Despite the committed action plans and several initiatives by the South African National Department of Health, there are ongoing medicine stock-outs at public health facilities across the country and this affects thousands of people. To explore this problem, this study explored pharmacists’ perceptions about factors contributing to stock-outs of essential medicines at a tertiary hospital in South Africa. Methods A qualitative cross-sectional study was conducted among pharmacists at a tertiary hospital in South Africa. Participants were purposively sampled and due to data saturation, 8 pharmacists participated in the study. Semi-structured, face-to-face interviews were used to collect data. Interviews were recorded and transcribed verbatim and analyzed using Tesch’s open coding process. Trustworthiness of data was measured through transferability, confirmability, credibility, and dependability. Results The participants included five procurement pharmacists, one stock controller pharmacist, one receiving pharmacist, and one contract pharmacist. All participants held a Bachelor of Pharmacy degree. Shortage of resources coupled with poor procurement processes affected the availability of medicines and hampered service delivery. Inconsistent deliveries from the Provincial Pharmaceutical Depot to hospitals and clinics as well as poor communication between stakeholders were also perceived as factors contributing to stock-outs of medicines. Conclusions Medicines supply chain management within the hospital has several gaps and shortcomings. The hospital should invest in strengthening the procurement and supply chain processes to ensure the availability of medicines. Recommendations To improve the availability of essential medicines, pharmacists and supply chain officers should receive continuous training on procurement processes. Formal communication forums to address challenges encountered in the provision of essential medicines should be established and sustained.